Magnetic Field Interactions of Military and Law Enforcement Bullets at 1.5 and 3 Tesla. Issue 7 (1st July 2016) - Diallo, Idris; Auffret, Mathieu; Attar, Lakdar; Bouvard, Elise; Rousset, Jean; Salem, Douraied Ben
ABSTRACT: Objectives: There are significant numbers of military and law enforcement bullets containing ferromagnetic materials. This study aimed to assess the magnetic field interactions for a representative sample of military and law enforcement ballistic objects at 1.5 and 3 tesla (T) to create a magnetic resonance imaging (MRI) compatibility database. Methods: Twenty-nine different bullets underwent MRI evaluation. The deflection angle method and a qualitative torque scale were used. The samples were representative of those commonly used in the North Atlantic Treaty Organization (NATO) military forces (e.g., 5.56 mm NATO), law enforcement agencies (e.g., 9 mm Parabellum), and encountered in war injuries and crime-related trauma (e.g., 7.62 mm Kalashnikov). Results: At all static magnetic field strengths, all non-nickel- and nonsteel-containing bullets exhibited no movement (deflection angle = 0°; torque = 0), whereas eight bullets containing steel core, steel jacket, or nickel jacket exhibited substantial magnetic field interactions over and above what might be regarded as safe in vivo (deflection angle = 90°; torque = 4+). Conclusion: Military and law enforcement non-nickel- or nonsteel-containing bullets appear to be safe for patients in MRI system at 1.5 and 3 T. On the other hand, nickel- and steel-containing bullets exhibit movements that are considered potentially unsafe for patients in an MRI environment.